P172 Challenges of Measuring the Uptake of National Public Health Guidance in the UK: A New Methodology. (15th August 2013) - Lea, R; Griffiths, P; Moore, V
Abstract : Background: We use published evidence to measure the uptake of national public health guidance recommendations. Available sources of uptake include national audits and reports, and peer reviewed journal articles. These are summarised and uploaded to an online database. This database is used to inform several streams of work in our organisation, including an internal review decision process for public health guidance. Identifying sources of uptake information in this area is challenging. Objectives: To assess the existing information on the database, and report on the effectiveness of a new approach to identifying potential sources of uptake information. Methods: An evaluation of public health uptake sources on the database was conducted, and a stakeholder mapping tool developed, which was used to systematically search for sources of uptake information. Stakeholders were contacted to provide information. Existing literature search strategies were reviewed and revised. Following these actions, the database was updated with the new sources and the impact of the exercise assessed. Results: The evaluation of the current database highlighted significant gaps regarding information relating to the uptake of public health guidance. Use of the methods outlined above identified a substantial amount of new information and a large number of potential sources of uptake for future reference. Discussion: The uptake of public health guidance is increasingly in the spotlight for the NHS, and knowing if recommendations have been implemented is helpful when deciding if guidance needs to be reviewed and updated. It is therefore important to have an accurate picture of uptake.